Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Karyawan yang Dimediasi Kepuasan Kerja Pada PT Sari Segar Husada Lampung Selatan - Mulana Simatupang, Baginda; Hayati, Keumala (Shofanah Media Berkah, 2023)
PT Sari Segar Husada Lampung Selatan is one of Indonesia's largest coconut product manufacturers. The issue around PT Sari Segar Husada Lampung Selatan revolves around transformational leadership and the lack of employee job satisfaction, as evidenced by the decline in employee performance. The company acknowledges the importance of job satisfaction from leadership, understanding that high performance contributes to achieving corporate goals. This research aims to analyze the influence of transformational leadership on employee performance, mediated by job satisfaction at PT Sari Segar Husada Lampung Selatan. This research employs a quantitative approach and is analyzed using multiple linear regression analysis. The data for this study were obtained from the questionnaire administered to 153 employees at PT Sari Segar Husada Lampung Selatan, utilizing SPSS 27 software. The findings of this research support the proposed hypothesis that transformational leadership has a positive and significant impact on employee performance, mediated by job satisfaction at PT Sari Segar Husada Lampung Selatan. The implications of this study suggest that leaders at PT Sari Segar Husada Lampung Selatan should value each employee's contribution, maintain a positive attitude toward employee performance achievements, and prioritize well-being to assist employees in achieving and sustaining job satisfaction.